KONTROL SOSIAL TERHADAP FUNGSI BALAI ADAT AIR MOLEK DI KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU - Anggi Novita Dewi; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research was conducted in Candirejo Village, Pasir Penyu Distric, Indragiri Hulu Subdistric. The problem in this study is, how to manage the Balai Adat how social control over the function of the Balai Adat. This research uses descriptive qualitative research methods using purposive sampling technique followed by snowball sampling. The subject numbered 7 (seven) people, where initially researchers only interviewed 3 subjects, namely the LAM Area Pasir Penyu, DPH LAM Area Pasir Penyu , LAM subdistric Indragiri Hulu. Then by using snowball technique which is the addition of a subject that is the Government, The Police, PJ traders, and parking attendants. Data collection uses observation techniques, in-depth interview and decomentation. The results in this study explain that in Pasir Penyu Subdistrict has Air Molek customary hall which is a hybrid of PT Tunggal Perkasa Plantations, the building of the Balai Adat is very grand but so far there is no management because the legality is not clear so that it is neglected and misused as a place of deviation of behavior that results in changes to the Balai Adat the weak social control of the LAM Area Pasir Penyu and other related parties in solving this problem so that irregularities still occur. It is hoped that the Balai Adat can be active again so that socio-cultural activities can be embraced in the building. Keywords : Social Control, Balai Adat, Deviant Behavior